2005
DOI: 10.1111/j.1365-2567.2004.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte isolation methods influence cytokine production from in vitro generated dendritic cells

Abstract: SummaryThere is growing interest in the in vitro generation of dendritic cells (DC) from peripheral blood monocytes, but the effect of the method chosen to isolate CD14 + monocytes for subsequent DC generation is poorly documented. The method used to isolate monocytes may have an impact on the subsequent function of DC by affecting their ability to express costimulatory molecules (CD80/86), maturation marker (CD83) and/or to produce important immunomodulatory cytokines. In this study, we show that the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 39 publications
3
110
0
2
Order By: Relevance
“…Chieppa et al (42) have reported that cross-linking of the mannose receptor on MDDC induces the production of anti-inflammatory cytokines and produces chemokines that direct Th2 and regulatory T cells and negatively regulate Th1 polarization. It has also been reported that MDDC derived from monocytes isolated by positive selection via anti-CD14 microbeads had a reduced capacity to produce IL-12, IL-10, and TNF-␣ in response to LPS stimulation as compared with MDDC generated from monocytes isolated by plastic adherence (43). In the case of PDC, cross-linking HLA-DR on CD40L-matured PDC, but not freshly isolated cells, has been shown to induce apoptosis of these cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Chieppa et al (42) have reported that cross-linking of the mannose receptor on MDDC induces the production of anti-inflammatory cytokines and produces chemokines that direct Th2 and regulatory T cells and negatively regulate Th1 polarization. It has also been reported that MDDC derived from monocytes isolated by positive selection via anti-CD14 microbeads had a reduced capacity to produce IL-12, IL-10, and TNF-␣ in response to LPS stimulation as compared with MDDC generated from monocytes isolated by plastic adherence (43). In the case of PDC, cross-linking HLA-DR on CD40L-matured PDC, but not freshly isolated cells, has been shown to induce apoptosis of these cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, LPS from E. coli has been shown to induce both IL-10 and IL-12 production in the murine models. [56][57][58][59][60] In the human system, the production of IL-12 in response to LPS has been shown to be variable and is affected by the way that DCs are generated 61 and by the amount of serum used in the culture media. 62 In addition, the amount of IL-12 produced in response to LPS can be affected by the amount of IL-10 endogenously produced.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other investigators have found that LPS stimulates intestinal epithelial cells to produce TNF 22,23 and PAF. 24 Thus, it is possible that LPS may directly stimulate enterocytes to express CXCL2 via the activation of NFjB, and this effect may be mediated via endogenous production of TNF and PAF.…”
mentioning
confidence: 99%